2016
DOI: 10.1136/bmjopen-2016-011165
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study of the regional quota system of Japanese medical schools and prefecture scholarship programmes: a study protocol

Abstract: IntroductionGiven the shortage of physicians, particularly in rural areas, the Japanese government has rapidly expanded the number of medical school students by adding chiikiwaku (regional quotas) since 2008. Quota entrants now account for 17% of all medical school entrants. Quota entrants are usually local high school graduates who receive a scholarship from the prefecture government. In exchange, they temporarily practise in that prefecture, including its rural areas, after graduation. Many prefectures also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…However, one study of Japanese rural doctors reported that having a rural origin was not related to intention to continue to their career in a rural area in a multivariate analysis (Matsumoto et al 2005). Though the Japanese government has started expanding the number of medical school entrance exams with a reginal quota since 2008 as previously mentioned (Matsumoto et al 2016), the scholarships are mainly provided by prefectures. Thus, rural medicine has been considered as a unit of the prefecture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one study of Japanese rural doctors reported that having a rural origin was not related to intention to continue to their career in a rural area in a multivariate analysis (Matsumoto et al 2005). Though the Japanese government has started expanding the number of medical school entrance exams with a reginal quota since 2008 as previously mentioned (Matsumoto et al 2016), the scholarships are mainly provided by prefectures. Thus, rural medicine has been considered as a unit of the prefecture.…”
Section: Discussionmentioning
confidence: 99%
“…Japanese rural areas have suffered from a shortage of physicians for several decades (Tanihara et al 2011). Since it has been reported that a large number of physicians who grew up in rural areas subsequently stayed in rural areas (Magnus and Tollan 1993), the Japanese government started expanding the number of medical school entrance places with a regional quota from 2008 (Matsumoto et al 2016). However, since Japanese medical education lasts six years, and several years more is needed to be a full-fledged physician, making sure that those students who enter medical school as part of the rural quote actually continue to work as rural physicians is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition to that, a regional scholarship system imitating the program of Jichi Medical University has been attempted by medical schools in the whole country, and it reached 17% of the entrance students of medical departments in 2004. 22 Medical experience in remote grounds after graduation…”
Section: Inequality In Distribution Of Physiciansmentioning
confidence: 99%
“…32 In the efforts in Japan, the above-mentioned Jichi Medical University program boasts a high obligation compliance rate, but it is still long before achieving the goal of the regional quota system started by each prefecture since 2004. 22…”
Section: Lending Of Scholarship On Condition Of Employment In Remote mentioning
confidence: 99%
“…Regional quotas, chiikiwaku , were first introduced, on a full scale, into medical schools, in 2009. A medical school's regional quota has three characteristics: (i) special admission different from the usual entrance examination, (ii) scholarships given by the home prefecture, and (iii) obligatory service in the home prefecture after graduation (usually a requirement of some years of rural service) . Jichi Medical University, established in 1972 solely to produce rural doctors, has the similar scholarship system and was used as the model for the regional quotas.…”
Section: Introductionmentioning
confidence: 99%